Training and development issues in Malaysia / Syed Jamal Abdul Nasir Syed Mohamad - Syed Mohamad, Syed Jamal Abdul Nasir (Universiti Teknologi MARA Cawangan Pahang, 2001)
This paper is discussing the issues in training and development in Malaysia Issues like changing in the nature of work force, attitude of the participants, employer's policy and environmental factors are very dominant in shaping the culture of training and development activities in Malaysia. Malaysia needs to take serious attention and consideration towards training and development programs in aiming to be an industrialized nation in 2020.